Antibacterial Activity of Plant-based Essential Oils against Uropathogenic Bacteria: A Systematic Review - A, Apostol; Bercede, Almirah M,; H, Daniel; D, Dizon; D, Christen Amber; E, Ebonite; O, Mia Sherrie; G, Guiao; P, Franchesca Louise; N, Nefulda; F, Stephen Darren; N, Nepomuceno; et al. (Asian Journal of Biological and Life Sciences)
Since urinary tract infections are still prevalent in today’s world, the authors sought to examine and summarize current and existing data of essential oils’ antibacterial activity and efficacy against a range of uropathogenic bacteria in order to educate the public about their presence and give additional information for future studies. Essential oil components have been studied in a variety of aromatic and medicinal plants. These are concentrated extracts of flowers and plants. To investigate if essential oils have a synergistic impact against human infections, they can be extracted and evaluated separately or in combination. This systematic review looks at previously recognized uropathogenic bacteria associated with infections in the urinary tract and other uropathogenic disorders that have been studied. This article discusses two types of bacteria: gram positive and gram-negative bacteria. Following the eligibility criteria, the authors conducted a systematic evaluation of literature concerning essential oils and their antibacterial efficacy against uropathogenic bacteria. Only 1,525 of the 1,574 articles found passed the screening process, and only 26 satisfied the inclusion criterion. When it comes to essential oil treatment, S. aureus is the most susceptible of all the gram-positive bacteria. In the meanwhile, the gram-negative bacteria E. coli was shown to be the most susceptible of all gram-negative bacteria. Essential oils appear to be useful medicinal plants for preventing bacterial development, according to current findings. Considering resistance to various antibiotics has become a severe concern in the recent years, the author suggests that new medical treatment for these diseases be created or improved.
Keywords: Essential oils; Susceptible; Synergistic; Urinary tract infection; Uropathogenic bacteria